miR-223-3p and miR-24-3p as novel serum-based biomarkers for myotonic dystrophy type 1 - Koutalianos, Demetris; Koutsoulidou, Andrie; Mytidou, Chrystalla; Kakouri, Andrea C.; Oulas, Anastasis; Tomazou, Marios; Kyriakides, Tassos C; Prokopi, Marianna; Kapnisis, Konstantinos; Nikolenko, Nikoletta; Turner, Chris; Lusakowska, Anna; et al. (My University, 2021)
Myotonic dystrophy type 1 (DM1) is the most common adult-onset muscular dystrophy, primarily characterized by muscle wasting and weakness. Many biomarkers already exist in the rapidly developing biomarker research field that aim to improve patients’ care. Limited work, however, has been performed on rare diseases, including DM1. We have previously shown that specific microRNAs (miRNAs) can be used as potential biomarkers for DM1 progression. In this report, we aimed to identify novel serum-based biomarkers for DM1 through high-throughput next-generation sequencing. A number of miRNAs were identified that are able to distinguish DM1 patients from healthy individuals. Two miRNAs were selected, and their association with the disease was validated in a larger panel of patients. Further investigation of miR-223-3p, miR-24-3p, and the four previously identified miRNAs, miR-1-3p, miR-133a-3p, miR-133b-3p, and miR-206-3p, showed elevated levels in a DM1 mouse model for all six miRNAs circulating in the serum compared to healthy controls. Importantly, the levels of miR-223-3p, but not the other five miRNAs, were found to be significantly downregulated in five skeletal muscles and heart tissues of DM1 mice compared to controls. This result provides significant evidence for its involvement in disease manifestation.
Keywords: miRNAs; Small extracellular vesicles; DMSXL mice; RNA-seq; Biomarkers; Heart; Muscle; Myotonic dystrophy; Serum; myomiRs